THE EFFECT OF SELF-CONCEPT, SELF-EFFICIENCY AND WORK MOTIVATION ON THE PERFORMANCE OF MI TEACHERS IN NIAS ISLANDS - Syaripuddin Daulay; Wahyudin Nur Nasution; Mesiono Mesiono (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
This study aims to determine the effect of self-concept, self-efficacy and work motivation on the performance of MI teachers throughout the Nias Islands. This study uses a quantitative approach with a population of 220 MI teachers throughout the Nias Islands, and a sample of 87 teachers through the Harry King Nomogram. The research instrument is a questionnaire using a Likert scale. Data analysis used path analysis, with stages of normality test, homogeneity test, linearity test. Then test the significance of the regression and the independence test between Exogenus variables. The results of the study found that (1) Self-concept has a direct positive effect on work motivation of Madrasah Ibtidaiyah teachers throughout the Nias Islands, by 8%, (2) Self-efficacy has a direct effect on work motivation of Madrasah Ibtidaiyah teachers throughout the Nias Islands by 11.2%; (3) Self-concept has a direct effect on the performance of Madrasah Ibtidaiyah teachers throughout the Nias Islands by 11.9%; (4) Self-efficacy has a direct effect on the performance of Madrasah Ibtidaiyah teachers throughout the Nias Islands by 12.6%; (5) Self-concept has an indirect effect on the performance of Madrasah Ibtidaiyah teachers throughout the Nias Islands through work motivation of 1.5%; (6) Self-efficacy has an indirect effect on the performance of Madrasah Ibtidaiyah teachers throughout the Nias Islands through work motivation of 0.8%; and (7) work motivation has a direct effect on the performance of Madrasah Ibtidaiyah teachers throughout the Nias Islands by 11%.